Frequency of Various Risk Factors for Meconium Aspiration Syndrome (Medical Forum Monthly, 2024)
Objective: To study the frequency of various factor leading to meconium aspiration syndrome.Study Design: Descriptive / Cross sectional study.Place and Duration of Study: This study was conducted at the Department of Pediatrics Medicine Nishtar Hospital Multan from October 8, 2016 to April 8, 2017.Materials and Methods: The non-probability, consecutive sampling technique was used. Newborns having staining of vocal cords and respiratory distress were included in this study. ABG and X-ray Chest was done in all neonates. Factors like, Post-term pregnancy, IUGR, thick meconium, low APGAR score at 1 and 5 minutes were noted. All the collected data was entered and analyzed on SPSS version 23. Chi square and T test were used to check significant relation of risk factors with meconium aspiration syndrome. P value of <0.05 was consider significant.Results: Among total enrolled 150 babies, the mean age of babies was 37.37±18.96 hours, the male to female ratio of the babies was 1.03:1. The mean maternal age was 28.85±6.602 years. The thick meconium was observed in 89(59.33%) patients, 79(52.7%) patients went through vaginal delivery, postdate pregnancy was noted in 68(45.3%) patients, IUGR was observed in 52(34.7%) patients and poor APGAR score at 1 min was noted in 79(52.7%) patients.Conclusion: The observations of our study revealed that Meconium aspiration syndrome has significant relation with maternal age(P value 0.000), postdated pregnancy (P Value 0.001), IUGR (P value 0.021), poor APGAR score at 5 minutes(P value 0.034), and thick meconium (P value 0.000).